The effect of spin in swing bowling in cricket: model trajectories for spin alone. (14th January 2015) - Robinson, Garry; Robinson, Ian
Abstract: In 'swing' bowling, as employed by fast and fast-medium bowlers in cricket, back-spin along the line of the seam is normally applied in order to keep the seam vertical and to provide stability against 'wobble' of the seam. Whilst spin is normally thought of as primarily being the slow bowlerʼs domain, the spin applied by the swing bowler has the side-effect of generating a lift or Magnus force. This force, depending on the orientation of the seam and hence that of the back-spin, can have a side-ways component as well as the expected vertical 'lift' component. The effect of the spin itself, in influencing the trajectory of the fast bowlerʼs delivery, is normally not considered, presumably being thought of as negligible. The purpose of this paper is to investigate, using calculated model trajectories, the amount of side-ways movement due to the spin and to see how this predicted movement compares with the total observed side-ways movement. The size of the vertical lift component is also estimated. It is found that, although the spin is an essential part of the successful swing bowlerʼs delivery, the amount of side-ways movement due to the spin itself amounts to a few centimetres or so, and is therefore small, but perhaps not negligible, compared to the total amount of side-ways movement observed. The spin does, however, provide a considerable amount of lift compared to the equivalent delivery bowled without spin, altering the point of pitching by up to 3 m, a very large amount indeed. Thus, for example, bowling a ball with the seam pointing directly down the pitch and not designed to swing side-ways at all, but with the amount of back-spin varied, could provide a very powerful additional weapon in the fast bowlerʼs arsenal. So-called 'sling bowlers', who use a very low arm action, can take advantage of spin since effectively they can apply side-spin to the ball, giving rise to a large side-ways movement, cm or more, which certainly is significant. For a given amount of spin the amount of side-ways movement increases as the bowlerʼs delivery arm becomes more horizontal. This technique could also be exploited by normal spin bowlers as well as swing bowlers.